Pengelolaan Pengelolaan manajemen sumber daya manusia di era digital: Rekrutmen, pengorganisasian, dan perspektif dalam islam - Nursafana, Ely Irma (Maliki Interdisciplinary Journal, 2026)
The rapid development of digital technology has significantly transformed human resource management (HRM) practices within organizations. These changes affect recruitment processes, work organization, and employee development in order to respond effectively to dynamic business environments. Human resources are no longer viewed solely as operational support, but as strategic assets with the ability to learn, adapt, and innovate. Therefore, the implementation of effective and sustainable HRM systems is essential in the digital era. In addition to technological and professional approaches, Islamic values also play an important role in guiding human resource management through principles such as justice, integrity, responsibility, social accountability, and ethical leadership. The integration of digital technology with Islamic values is expected to create a productive, ethical, and harmonious work environment while supporting organizational sustainability. By combining modern management practices with moral and religious principles, organizations can enhance employee performance, achieve optimal organizational goals, and maintain competitiveness in an increasingly complex digital landscape.